2012
DOI: 10.1143/jjap.51.06fl01
|View full text |Cite
|
Sign up to set email alerts
|

New Laser-Scan Exposure System for Delineating Precise Helical Patterns onto Sub-50-µm Wires

Abstract: A new laser-scan exposure system for patterning onto fine wires and pipes with diameters as small as 40 m was developed. New schemes for vertically holding specimens were adopted, and improved optics of imaging and in situ observation were used. In addition, specially contrived halfvacuum support guides were attached, and a short-wavelength violet laser with a wavelength of 408 nm was also attached. Because the laser beam spot was kept steady at a constant size by the improved half-vacuum support guide with tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Concerning exposure systems for printing or delineating patterns on a cylindrical specimen, various research results have been reported [14][15][16][17][18]. The authors have developed some systems also except the above mentioned ones [19][20][21][22]. However, the system used for this research had a large advantage that arbitrary intricate patterns were printable in a same exposure time without depending on the pattern density and complicatedness.…”
Section: Resist Patterning Using Synchronized Scan Rotation Lithographymentioning
confidence: 99%
“…Concerning exposure systems for printing or delineating patterns on a cylindrical specimen, various research results have been reported [14][15][16][17][18]. The authors have developed some systems also except the above mentioned ones [19][20][21][22]. However, the system used for this research had a large advantage that arbitrary intricate patterns were printable in a same exposure time without depending on the pattern density and complicatedness.…”
Section: Resist Patterning Using Synchronized Scan Rotation Lithographymentioning
confidence: 99%
“…Delineation of multi-slit patterns using laser-scan lithography was investigated using the latter exposure system developed in the past research [18]. The exposure wavelength was 408 nm.…”
Section: Delineation Of Slit Patterns Using Laser-scan Lithographymentioning
confidence: 99%
“…In our laboratory, two laser-scan exposure systems were developed for delineating patterns on wires and pipes placed horizontally and vertically, respectively [1,18]. Using the former exposure system, in which the specimens were set horizontally, nickel coil springs were fabricated by forming helical resist patterns on a stainless-steel wire with diameters of 80-100 µm using the laser-scan lithography, and electroplating nickel between the resist patterns [1].…”
Section: Introductionmentioning
confidence: 99%
“…To answer the requirement, various researches on developing lithography systems for replicating or delineating patterns on cylindrical materials were carried out [1][2][3][4][5][6][7]. The authors also developed laser-scan exposure systems onto fine wires and pipes with diameters of 40-500 µm [8][9][10][11][12][13]. It was demonstrated that very precise patterns were arbitrarily delineated on surfaces of such very fine cylindrical materials.…”
Section: Introductionmentioning
confidence: 99%